Accessibility of Higher Education for Women as a Means of Career Development: A Case Study of Students at the Kartini Rembang Open University Service Center - Yuyun, Yuyun; Utami, Intiyas; Lestari, Etty Puji (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to analyze the accessibility of higher education for women as a means of career development, among students at the Kartini Open University Service Center (SALUT) in Rembang. This research is in line with the principles of the Sustainable Development Goals (SDGs), specifically goal 4 on quality education and goal 5 on gender equality, which emphasize the importance of learning opportunities for all without exception. The approach used is a qualitative case study method. Data were obtained through interviews, observations, and documentation, then analyzed descriptively through the process of reduction, presentation, and drawing conclusions. The results of the study indicate that a flexible learning system provides opportunities for women to continue their studies without neglecting family or work responsibilities. Internal factors such as motivation, awareness of the importance of education, self-confidence, and aspirations are the main drivers. Meanwhile, external factors such as family support, social environment, education policies, and workneeds also strengthen access to higher education. The results of this study are expected to be an academic and practical contribution in understanding and strengthening the role of higher education as a means of emancipation, career development, and empowerment of women through more inclusive and equitable access.